2007
DOI: 10.1097/01.cnq.0000278922.21821.52
|View full text |Cite
|
Sign up to set email alerts
|

Scope Creep

Abstract: The finite boundaries of the scope of nursing practice are constantly changing. One could expect that with new technology and advances in science, the interventions and assessments nurses perform will change over time. The practice of nursing is governed by nursing, however, it is often challenged by our partners in medicine, and frequently driven by time constraints or reimbursement issues. This article reviews a case example in which nurses were asked to expand their practice to assume responsibility for dut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Few boards of nursing and professional standards address deep sedation by RNs or have incorporated standards from organizations such as the ASA that restrict RNs from administering propofol and other anesthetic medications into their position statements. However, this study found that 13.69% of RNs in the sample provided deep sedation (see Table 5), demonstrating that RNs are already providing care that conflicts with recommendations by the ASA and exceeds the scope of practice set by some state boards of nursing (Davidson, Bloomberg, & Burnell, 2007). …”
Section: Discussionmentioning
confidence: 80%
“…Few boards of nursing and professional standards address deep sedation by RNs or have incorporated standards from organizations such as the ASA that restrict RNs from administering propofol and other anesthetic medications into their position statements. However, this study found that 13.69% of RNs in the sample provided deep sedation (see Table 5), demonstrating that RNs are already providing care that conflicts with recommendations by the ASA and exceeds the scope of practice set by some state boards of nursing (Davidson, Bloomberg, & Burnell, 2007). …”
Section: Discussionmentioning
confidence: 80%